Use of an amikacin‐infused collagen sponge concurrent with implant removal for treatment of tibial plateau leveling osteotomy surgical site infection in 31 cases. Issue 5 (5th June 2019) - Lee, Sylvia J.; Frederick, Steven W.; Cross, Alan R.
Abstract: Objective: To report the use and long‐term outcome of dogs with surgical site infection (SSI) after tibial plateau leveling osteotomy (TPO), treated with an amikacin‐infused collagen sponge and implant removal. Study design: Retrospective study. Animals: Thirty‐one client‐owned dogs. Methods: Medical records were reviewed for dogs with SSI after a TPLO that were treated with surgical implant removal and concurrent implantation of an amikacin‐infused collagen sponge. Relevant clinical and surgical data were recorded. The TPLO implants were routinely removed; the surgical site was swabbed for culture. The sponge was aseptically infused with amikacin prior to implantation. Postprocedure examinations consisted of visual inspection of the incision by the surgeon and lameness scoring. Results: Thirty‐one dogs met all inclusion criteria. Median follow‐up time was 687 days. Short‐term examination after implant removal and sponge implantation revealed uneventful incisional healing in 24 dogs. Six (19.4%) dogs exhibited inflamed incision sites a median of 4 days (range, 3–9) postoperatively that resolved without additional treatment. One (3.2%) dog required empirical antibiotic treatment 7 days postoperatively but was lost to long‐term follow‐up. Long‐term follow‐up examination revealed no clinical evidence of SSI recurrence and no lameness in the remaining 30 cases. Conclusion: Surgical implant removal and implantation of an absorbable collagen sponge infused with amikacin alone was an effective treatment for postoperative TPLO SSI. Clinical significance: This procedure had a 96.8% long‐term resolution of SSI. It should be considered as a treatment option for TPLO SSI.